Knowledge, attitude and practice towards scientific research among undergraduate students of a medical college in Delhi - Singh, Sunil Kumar; Mishra, Suruchi; Khokhar, Anita; Bharti, Aakanksha; Sharma, Manila (International Journal Of Community Medicine And Public Health, 2020)
Background: Scientific research forms an important foundation for producing doctors with an understanding of evidence-based medicine. Medical education in India over a period has largely remained unchanged with a very low emphasis on research and publication. Objective of the study was to assess the knowledge, attitude and practice towards scientific research among undergraduate students of a medical college in Delhi, India. Methods: A cross sectional study was planned among 240 undergraduate students from five semesters of medical college in New Delhi. The questionnaire consisted of questions about identification data, knowledge, attitude and practices of scientific research. Data was analyzed by SPSS software version 21.0 and for qualitative data analysis Chi-square test was used. Results: Mean age of study subjects was 20.68±1.87 years and more than half (59.6%) of them were males and (40.4%) were females. Out of 240 participants, only (13.5%) had excellent knowledge about scientific research. Majority (89.6%) of them felt that research work should be a part of the medical curriculum. About one fourth (22.9%) of study participants had done a scientific research. Age of study participants and better knowledge were found significant predictors of conducting research among study participants. Conclusions: This study concludes that only few study participants had excellent knowledge and practice scientific research but majority of them had positive attitude towards research. So, there is a need to increase awareness about scientific research from an early level in the curriculum among study population.